The role of human disturbance in island biogeography of arthropods and plants: an information theoretic approach. (9th May 2015) - Nakamura, Akihiro; Burwell, Chris J.; Lambkin, Christine L.; Katabuchi, Masatoshi; McDougall, Andrew; Raven, Robert J.; Neldner, V. John
Abstract Aim Recent progress in island biogeography indicates that classical island biogeography alone cannot encapsulate the complex and dynamic nature of island biogeographical processes. Factors such as habitat complexity and connectivity, and in the face of the Anthropocene, human disturbance and invasive species, may influence insular communities. The relative importance of these factors, however, may differ among groups of biota. Here we employed an information theoretic approach to investigate factors likely to explain patterns in species richness and assemblage composition of five different groups of arthropods (ants, beetles, flies, spiders and cockroaches) and native and exotic plants within an insular community. Location Capricornia Cays located at the southern end of Great Barrier Reef, eastern Australia. Methods Arthropods were sampled from 14 cays using pitfall and Malaise traps and hand collecting. Plants were comprehensively surveyed on each island. We used univariate and multivariate generalized linear models with a model averaging technique, to calculate summed Akaike weights which quantified the relative importance of predictor variables in explaining variation in species richness and assemblage composition. Results We found that infestation of the invasive ant Pheidole megacephala was negatively correlated with the species richness of ants, beetles and flies. Unlike species richness, only the assemblage composition of ants was related to P. megacephala infestation. Assemblage composition of other arthropod groups and plants was related to various factors, including island size (native plants), native plant species richness (beetles, flies and spiders) and presence of human disturbances (exotic plants and cockroaches). Main conclusions The information theoretic approach proved useful in determining the relative likelihood of factors influencing both univariate and multivariate data of insular fauna and flora. The results demonstrated that human disturbance and proliferation of invasive species can override other biogeographical processes. The relative importance of these factors, however, varied depending on the taxonomic groups studied.